The Knowledge Level of Market Information by Farmers and The Influencing Factors. (July 2020) - Putra, D E; Hariono, B; Utami, R R M M D; Riskiawan, H Y; Setyohadi, D P S
Abstract: This study aims to measure the knowledge level of market information by rubber and what factors can influence it. This study also finds out whether there is a gap or the difference between the mastery at the farm level with the mastery of information at the traders level. This research was located in Sintang District which is one of rubber production center in West Kalimantan. The number of respondents was determined by 153 farmers of respondents distributed in each location. Frequency analysis, chi-square and multiple linear regression were used to answer the objectives. The results showed that the level of mastery of market information by rubber farmers is included in the medium to the high category for price indicators, form, time and place. Then the data shows that there was no gap or difference in the mastery of market information between farmers and traders in general, but for the mastery of price information obtained results, there was a gap between farmers and traders. The factors affecting the mastery of rubber farmers' market information are age, income from farming, distance from the house to the factory, electronic communication media, online communication media and utilization of information source from the internal factory (foreman/manager).